Panoramic Indicators of Nepalese Agriculture - Bhattarai, Dilliram (Tribhuvan University Journal, 2011)
Not available. Key words: Agrarian country; Agro based industries; Depend on agriculture; Nepal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 69-77 Uploaded date: 29 April, 2011